Defining the boundaries of structural texture region in the space of transform with distributional scaling functions - Polyakova, Marina; Krylov, Victor; Gulyaeva, Natalya (Видавництво Львівської політехніки, 2012)
In this paper the method for determination of the structural texture region boundaries is proposed.
Keywords: distribution scaling function; structure texture image; underlining transform